TED talk and YouTube for English education: An autoethnographic study - Tran Thi, Hoang Nguyen (English Language Teaching Educational Journal, 2024)
Through a personal exploration using autoethnographic methodology, this study delves into the researcher’s experiences as both a student and a teacher, analyzing the benefits and limitations of integrating these social media tools into English education. Data collected through reflective journaling on the usage of these platforms reveals key themes regarding engagement, distractions, and overall academic performance. Ultimately, this study seeks to answer how these platforms have enhanced verbal skills and whether such experiences can be synthesized into lessons or activities to further assist other learners in their educational journeys. The findings point to both positive and negative impacts on teaching and learning development in ELT, with the positive impacts being processed into practical strategies for supporting teaching and learning.